A Critical Analysis of Mitchel Foucault’s Perspective on Governmentality and Higher Education - Gbenga Michael Adeyeye (E-Journal of Humanities, Arts and Social Sciences, 2024)
The article offers a thorough examination of Foucault’s notion of governmentality and its practical implications in empirical investigations, specifically within the realm of education. Utilising recent academic research, this analysis thoroughly evaluated the adoption and application of the concept, followed by an exploration of studies in the fields of education and health that adopt a governmentality perspective. By highlighting the historical aspect, this perspective challenges existing frameworks of these fields and uncovers alternative potentialities. This study addressed the need for empirical research that employs governmentality as an analytical framework, intending to clarify its effectiveness in comprehending power dynamics within societal institutions. In addition, it explored Foucault’s concept of governmentality and its development in modern literature, highlighting its complex and dynamic characteristics. Ultimately, it acknowledged criticisms of Foucault’s concept and proposed possible directions for future investigation, such as examining its influence on the evolution of capitalism and conducting education system studies tailored to specific periods. This paper makes a substantial contribution to academic research by offering a thorough analysis of Michel Foucault’s concept of governmentality and its application in the context of higher education. It improves understanding of power relations within educational institutions and emphasizes the influence of neoliberal policies on governance and educational practices.